Do Serum C-Reactive Protein Trends Predict Treatment Outcome in Patients with Knee Periprosthetic Joint Infection Undergoing Two-Stage Exchange Arthroplasty? - Sheng-Hsun Lee; Chun-Ting Chu; Chih-Hsiang Chang; Chih-Chien Hu; Szu-Yuan Chen; Tung-Wu Lu; Yu-Chih Lin (Diagnostics, 2022)
Two-stage exchange arthroplasty is the standard treatment for knee periprosthetic joint infection (PJI). This study aimed to determine whether serial changes in C-reactive protein (CRP) values can predict the prognosis in patients with knee PJI. We retrospectively enrolled 101 patients with knee PJI treated with two-stage exchange arthroplasty at our institution from 2010 to 2016. We excluded patients with spacer complications and confounding factors affecting CRP levels. We tested the association between treatment outcomes and qualitative CRP patterns or quantitative CRP levels. Of the 101 patients, 24 (23.8%) had recurrent PJI and received surgical intervention after two-stage reimplantation. Patients with a fluctuating CRP pattern were more likely to receive antibiotics for a longer period (p < 0.001). There was greater risk of treatment failure if the CRP levels were higher when antibiotics were switched from an intravenous to oral form (p = 0.023). The patients who received antibiotics for longer than six weeks (p = 0.017) were at greater risk of treatment failure after two-stage arthroplasty. Although CRP patterns cannot predict treatment outcomes, CRP fluctuation in the interim period was associated with longer antibiotic duration, which was related to a higher treatment failure rate.